The effectiveness of educational technology applications on adult English language learners' writing quality: a meta-analysis. Issue 1 (2nd January 2019) - Xu, Zhihong; Banerjee, Manjari; Ramirez, Gilbert; Zhu, Gang; Wijekumar, Kausalai (Kay)
Abstract: Learning to write well can be a significant contributor to English language proficiency. The large population of English language learners (ELLs) has highlighted the need for educational technology as an important support for the different approaches to writing instruction for ELLs. In this meta-analysis, we examined the effectiveness of educational technology applications on the writing quality of adult ELLs. Twenty-one independent studies from 16 publications were included in this review. Our findings confirmed that technology applications produce a large effect size (.93 and 1.28, fixed effect model and random effect model respectively) as compared to non-technology instructional methods. We conducted sub-group analyses with six substantive and methodological factors: type of technology, genre of writing, program duration, program intensity, measures outcome, and research design, and followed the analyses with research and pedagogical implications.